Direct Electron Transfer-Type Bioelectrocatalysis of Redox Enzymes at Nanostructured Electrodes - Adachi, Taiki; Kitazumi, Yuki; Shirai, Osamu; Kano, Kenji (Catalysts, 2020)
Direct electron transfer (DET)-type bioelectrocatalysis, which couples the electrode reactions and catalytic functions of redox enzymes without any redox mediator, is one of the most intriguing subjects that has been studied over the past few decades in the field of bioelectrochemistry. In order to realize the DET-type bioelectrocatalysis and improve the performance, nanostructures of the electrode surface have to be carefully tuned for each enzyme. In addition, enzymes can also be tuned by the protein engineering approach for the DET-type reaction. This review summarizes the recent progresses in this field of the research while considering the importance of nanostructure of electrodes as well as redox enzymes. This review also describes the basic concepts and theoretical aspects of DET-type bioelectrocatalysis, the significance of nanostructures as scaffolds for DET-type reactions, protein engineering approaches for DET-type reactions, and concepts and facts of bidirectional DET-type reactions from a cross-disciplinary viewpoint.